KNOWLEDGE ABOUT PREGNANCY DANGER SIGNS AMONG MOTHERS ATTENDING ANTENATAL CARE IN JUGAL HOSPITAL, HARARI REGIONAL STATE, ETHIOPIA, 2019 - Hussen, Arif (Public Health of Indonesia, 2019)
Background: Every pregnant woman faces the risk of sudden, unpredictable complication that could end in death or injury to mother or infant. Each year, approximately 287,000 women die from complications related to pregnancy and childbirth in developing countries. Maternal mortality ratio (MMR) in developing regions is 15 times (240/100,000 live births) higher than in developed regions (16/100,000live births)  Objective: The aim of this study was to determine the knowledge about pregnancy danger signs among mothers attending antenatal care in Jugal Hospital, Harari Regional State, Ethiopia.Methods: Institution based cross-sectional study design was conducted. A systematic random sampling technique was used to select study participants from pregnant mothers attending antenatal care during the time of data collection. Data were collected using a structured questionnaire and it was entered in to EPI Data version 3.1 software program and exported to SPSS version 20 software for analysis.Results: A total of 316 pregnant women were included in the study with a response rate of 86%. The study indicated that 44.67% of the respondents had knowledge on danger signs of pregnancy, and there was a significant association with the knowledge on danger signs of pregnancy and the age of the respondent and educational status of the respondent (P <0.05).Conclusion: The study finding shows that poor awareness about danger signs of pregnancy among antenatal care attendants in Jugal hospital, Harari Regional State. There was a significant association between educational status, the age of the mother and knowledge about pregnancy danger signs among mothers attending antenatal care.